The state of technology education : a European Commission perspective - Dow, Wendy; Dakers, John (Design and Technology Education: An International Journal, 2008)
This paper arises out of a consultancy to the European Commission. The commission had identified a problem with recruitment to Mathematics, Science and Technology (MST) subjects and careers across Europe and wished to explore existing examples of good practice in the field. The paper describes the methodology used in two phases of the consultancy which set out to identify examples of good practice and highlights the problems encountered in doing this with particular reference to Technology education. The paper then describes examples of good practice in Technology education provided and discusses some of the common problems encountered by European countries in developing an effective system of technology education across all sectors of the education system.